Determinants of Job-Finding Intentions Among Young Adults from 11 European Countries - Francisco Sim\~oes; Jale Tosun; Antonella Rocca (Social Indicators Research, 2022)
Abstract In this study we investigate the impact of individual, parental and social factors on young adults' job-finding intentions across countries and overall. We test our hypotheses by conducting binary logistic regressions on the basis of an original dataset that comprises responses from more than 5200 young adults and their parents from 11 European countries. Our findings show that individual factors are most decisive in shaping the job-finding intentions of young adults. Most importantly, being enrolled in education does not prevent young adults from lowering their aspirations with respect to anticipated earnings or finding more sophisticated jobs. Social factors, in terms of being socially involved or having more friends in employment, lead to stronger mobility intentions as well as to stronger intentions to improve skills or develop new ones. At the country level, and compared to Italian participants, who go through a longer school-to-work transition, participants from Northern or Central European countries, as well as from the United Kingdom, show weaker mobility intentions. In many of these countries, young adults are also more willing than their Italian counterparts to lower income aspirations, while being less inclined to lower their aspirations in terms of finding more sophisticated jobs. In a last step, we reflect on education as a means of improving professional aspirations and the need to offer adequate on-the-ground services to help young people through the school-to-work transition, especially in Southern European countries.
Keywords: 330; Education; Mobility; Professional expectations; School-to-work transition; Skills